2020
DOI: 10.1002/ghg.1956
|View full text |Cite
|
Sign up to set email alerts
|

Statistical based hydromechanical models to estimate poroelastic effects of CO2 injection into a closed reservoir

Abstract: In this study, a statistical‐based methodology is used to evaluate the poroelastic effects of injection during CO2 geologic sequestration in a closed reservoir. We constructed a series of hydromechanical models to evaluate the poroelastic effect of injection by quantifying total stress changes inside the reservoir, reservoir displacement, and surface uplift. The models are representative of closed carbonate reef reservoirs of the Michigan basin. A combination of experimental design for seven independent parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 66 publications
(140 reference statements)
0
8
0
Order By: Relevance
“…The pore pressure is the pressure borne or transmitted by the fluid in the rock, and the effective stress is the stress transmitted by the contact surface between the rock-solid particles. Many laboratory experiments have shown that the pore pressure P has different effects on deformation and failure of the fluid fully or partially saturated porous solid [29,30]. Both theoretical and experimental studies have shown that failure is controlled by the effective stress.…”
Section: Effective Stress Principle Of Rockmentioning
confidence: 99%
“…The pore pressure is the pressure borne or transmitted by the fluid in the rock, and the effective stress is the stress transmitted by the contact surface between the rock-solid particles. Many laboratory experiments have shown that the pore pressure P has different effects on deformation and failure of the fluid fully or partially saturated porous solid [29,30]. Both theoretical and experimental studies have shown that failure is controlled by the effective stress.…”
Section: Effective Stress Principle Of Rockmentioning
confidence: 99%
“…Fluid saturation and pore pressure changes in the reservoir due to CO 2 injection alter elastic wave velocities 4 . In situ stresses can also be changed in the reservoir due to the poroelastic response to CO 2 injection 5–7 . The amount of stress changes in the reservoir depends on the geomechanical properties of reservoir and surrounding formations, amount of injected CO 2 , and associated pore pressure changes 6,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Reservoir inflation, surface uplift, fracturing of the reservoir and/or caprock, fault activation, wellbore failure, and casing damage are examples of geomechanical‐related risks, which can have significant environmental consequences such as groundwater contamination due to CO 2 leakage, 3,4 and seismicity with possible ground motion due to fault activation 5–9 . Field tests, 2,10,11 laboratory experiments, 12–15 and geomechanical modeling 16–18 provide tools to evaluate the likelihood and severity of geomechanical responses. Before fluid injection, field tests can be used to characterize the hydromechanical characteristics of formations, fracture network parameters, as well as the state of stress in the caprock–reservoir formations 2,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Geomechanical modeling is essential to assess different aspects of the geomechanical‐related risks quantitatively and ensure safety and security of CO 2 storage. The objective of the geomechanical modeling is to estimate injection‐induced stress and strain of the reservoir, caprock, and the other overlying formations up to the Earth's surface 16–18,20,21 . These geomechanical responses can then be interpreted to assess geomechanical risks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation